2021
DOI: 10.4103/jehp.jehp_632_20
|View full text |Cite
|
Sign up to set email alerts
|

Establishing criterion validity for the Revised Critical Nutrition Literacy Tool in U.S. college students

Abstract: BACKGROUND: Critical nutrition literacy (CNL) plays an important role in how college students make everyday decisions about nutrition choices. Increasing CNL is an aim of many introductory nutrition courses, but there are limited instruments measuring this construct. This study aimed to assess the changeability of CNL and the relationship between CNL and markers of diet quality in young adults. DESIGN: This was a two-phase research project consisting of a nonexperimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
5
0
1
Order By: Relevance
“…Another previous study among Turkish 14-to-19-year-old omnivores reported a moderate level of critical nutrition literacy (31) , in agreement with our findings. Another study measuring critical nutrition literacy in US students (aged 18-24 years) (32) reported a mean score of 3•4, similar to our score of 3•7, using a comparable scoring system out of five (one indicated a lower level and five indicated a higher level of critical nutrition literacy). However, unlike our study, they divided the critical nutrition literacy score into three equally distributed groups to evaluate poor, moderate and high levels of critical nutrition literacy whereas we used score cut-offs to classify the groups.…”
Section: Critical Nutrition Literacysupporting
confidence: 81%
“…Another previous study among Turkish 14-to-19-year-old omnivores reported a moderate level of critical nutrition literacy (31) , in agreement with our findings. Another study measuring critical nutrition literacy in US students (aged 18-24 years) (32) reported a mean score of 3•4, similar to our score of 3•7, using a comparable scoring system out of five (one indicated a lower level and five indicated a higher level of critical nutrition literacy). However, unlike our study, they divided the critical nutrition literacy score into three equally distributed groups to evaluate poor, moderate and high levels of critical nutrition literacy whereas we used score cut-offs to classify the groups.…”
Section: Critical Nutrition Literacysupporting
confidence: 81%
“…The data extraction from the included literature in this mini-review is presented in Table 1 . The studies included describes tools published between 2017–2022, in which four studies (three different tools) measured food literacy ( 19 , 21 , 23 , 24 ) and five studies measured nutrition literacy or sub-dimensions of nutrition literacy ( 17 , 18 , 25 , 26 , 28 ). The mean age in the included studies ranged from 17–24 years, except for one previously mentioned study that did not report mean age ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies referred to nutrition literacy as a construct with three sublevels (functional, interactive, and critical nutrition literacy) (18,25,26,28) and considered to be a subset of health literacy (12). Four of the nine included studies in this mini-review used a tool that measured all three sublevels of nutrition literacy (17,18,25,26), while one of the included studies measured only two subset of nutrition literacy (functional and critical nutrition literacy) (28).…”
Section: Tools Used To Measure Nutrition Literacy (Sub-competence Of ...mentioning
confidence: 99%
“…Namun demikian, masih terdapat sedikit hasil penelitian yang dipublikasikan di Indonesia terkait konsep literasi gizi lebih luas sejak konsep literasi gizi ini dikenalkan di dunia. Sementara itu, upaya pendidikan gizi untuk peningkatan literasi gizi perlu diupayakan untuk menyasar peningkatan komponen interactive dan critical nutrition literacy karena komponen ini sangat penting untuk memampukan seseorang mengubah perilaku makannya (Bedoyan et al, 2021).…”
Section: Pendahuluanunclassified